Minimal invasive versus open esophagectomy for patients with esophageal squamous cell carcinoma after neoadjuvant treatments - Chen, Dongni; Wang, Weidong; Mo, Junxian; Ren, Qiannan; Miao, Huikai; Chen, Youfang; Wen, Zhesheng (BMC cancer, 2021)
Although previous studies have discussed whether the minimally invasive esophagectomy (MIE) is superior to open surgery, the data concerning esophageal squamous cell carcinoma (ESCC) patients underwent neoadjuvant treatment followed by radical resection is limited. The purpose of our study was to compare the short- and long-term clinical outcomes of the two surgical approaches in treating ESCC patients. Between January 2010 and December 2016, ESCC patients who had received neoadjuvant therapy and underwent Mckeown esophagectomy at our institute were eligible. The baseline characteristics, pathological data, short-and long-term outcomes of these patients were collected and compared based on the surgical approach. A total of 195 patients was included in the current study. Compared to patients underwent open surgery, patients underwent MIE had shorter operative time and less intraoperative bleeding (390 min vs 330 min, P = 0.001; 204 ml vs 167 ml, P = 0.021). In addition, the risk of anastomotic leakage was decreased in MIE group (20.0% vs 3.3%, P < 0.001), while the occurrence of other complications did not have statistical significance between two groups. Overall survival (OS) and disease-free survival (DFS) was no difference in patients received neoadjuvant chemotherapy between the two approaches. For the patients underwent neoadjuvant chemoradiotherapy, OS was significantly better in the MIE group (log rank = 6.197; P = 0.013). Minimally invasive Mckeown esophagectomy is safe and feasible for ESCC patients who underwent neoadjuvant therapy. MIE approach presented better perioperative results than open esophagectomy. The effect of surgical approaches on survival was depending on the scheme of neoadjuvant treatment.